How prices guide investment decisions under net purchasing - An empirical analysis on the impact of network tariffs on residential PV - Fabian Arnold; Samir Jeddi; Amelie Sitzmann (Institute of Energy Economics at the University of Cologne (EWI), 2021)
Within the regulation of net purchasing, investment incentives for residential PV depend on the remuneration for grid feed-in and the consumption costs that households can save by self-consumption. Network tariffs constitute a substantial part of these consumption costs. We use postcode-level data for Germany between 2009 and 2017 and exploit the regional heterogeneity of network tariffs to investigate whether they encourage to invest in PV installations and evaluate how the nonlinear tariff structure impacts residential PV adoption. Our results show that network tariffs do impact PV adoption. The effect has increased in recent years when self-consumption has become financially more attractive, and the results confirm the expectation that PV investments are driven by the volumetric tariff. Policy reforms that alter the share between the price components are, thus, likely to affect residential PV adoption. Further, with self-consumption becoming a key incentive, price signals can effectively support the coordination of electricity demand and supply in Germany.
Keywords: C33; D12; L51; Q42; 330; Network tariffs; PV investments; self-consumption; price perception; panel data; prosumer; non-linear prices